2021
DOI: 10.1136/bmjopen-2021-054479
|View full text |Cite
|
Sign up to set email alerts
|

Observing time effect of SSRIs on suicide risk and suicide-related behaviour: a network meta-analysis protocol

Abstract: IntroductionSuicide is a serious problem worldwide and 90% cases are associated with pre-existing or underlying mental illness. As a common treatment for depressive symptoms that suicidal people may receive, selective serotonin reuptake inhibitors (SSRIs) have been linked to a possible increase in suicide rates. Studies focusing on SSRIs and suicide have produced inconsistent results, suggesting that use of SSRIs decreases, increases, has no effect on suicide rates, or that the effect of SSRIs on suicide is ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Suicidal behavior is a feared and severe outcome in young patients using SSRIs [ 22 ]. We have detected a more than a 2-fold increased risk of suicide attempt/self-harm in the children and adolescents who were using (es)citalopram with poor metabolizing capacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Suicidal behavior is a feared and severe outcome in young patients using SSRIs [ 22 ]. We have detected a more than a 2-fold increased risk of suicide attempt/self-harm in the children and adolescents who were using (es)citalopram with poor metabolizing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, an international study of 243 patients found no differences between the phenotypes and suicidal behavior, as measured by clinical rating scales [ 24 ], while a post-mortem study showed an enrichment of CYP2C19 PMs and UMs among adult suicide victims who had tested positively for citalopram, compared with the population controls [ 25 ]. It should be noted that the use of (es)citalopram dropped to nearly 0 by 2021 [ 26 ] in children and adolescents since the warnings of the increased risk of suicidal behavior were issued in 2010 [ 22 ]. In 2021, fluoxetine and sertraline were the most frequently used antidepressants among children in Denmark [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have been conducted on the effect of antidepressants in treating depression and preventing suicide, and completely different results have been extracted. Some studies have reported a positive effect, 47–49 and others have said an adverse effect or lack of effectiveness of these drugs 50–52 …”
Section: Discussionmentioning
confidence: 99%